Functional Outcomes and Quality of Life after Redo Anastomosis in Patients With Rectal Cancer: An International Multicenter Comparative Cohort Study. Issue 7 (19th April 2021) - Westerduin, Emma; Elfeki, Hossam; Frontali, Alice; Lakkis, Zaher; Laurberg, Søren; Tanis, Pieter J.; Wolthuis, Albert M.; Panis, Yves; D'Hoore, Andre; Bemelman, Willem A.; Juul, Therese
Abstract : Supplemental Digital Content is available in the text. Abstract : BACKGROUND: Redo anastomosis can be considered in selected patients with persistent leakage, stenosis, or local recurrence. It is technically challenging, and little is known about the functional outcomes after this seldomly performed type of surgery. OBJECTIVE: The aim of this study was to compare functional outcomes and the quality of life between redo anastomosis and primary successful anastomosis following total mesorectal excision for rectal cancer. DESIGN: This study was designed as an international multicenter comparative cohort study. SETTINGS: The study was conducted in 3 tertiary referral centers in the Netherlands, Belgium, and France. PATIENTS: Patients undergoing redo anastomosis were compared with patients with a primary successful anastomosis after total mesorectal excision for rectal cancer. MAIN OUTCOME MEASURES: Low anterior resection syndrome score, European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ) C30, and EORTC QLQ-CR29 questionnaires were used to assess outcomes. RESULTS: In total, 170 patients were included; 52 underwent redo anastomosis and 118 were controls. Major low anterior resection syndrome occurred in 73% after redo anastomosis compared with 68% following primary successful anastomosis ( p = 0.52). The redo group had worse EORTC QLQ-CR29 mean scores for fecal incontinence ( p = 0.03) and flatulence ( p = 0.008). There were no differences in urinary ( p = 0.48) or sexual dysfunction, either in men ( p = 0.83) or in women ( p = 0.76). Significantly worse scores in the redo group were found for global health ( p = 0.002), role ( p = 0.049) and social function ( p = 0.006), body image ( p = 0.03), and anxiety ( p = 0.02). LIMITATIONS: This study is limited by the possible response bias. CONCLUSIONS: Redo anastomosis is associated with significantly worse quality of life compared with primary successful anastomosis. However, major low anterior resection syndrome was comparable between groups and should not be a reason to preclude restoration of bowel continuity in highly motivated patients. See Video Abstract at http://links.lww.com/DCR/B565 . RESULTADOS FUNCIONALES Y DE CALIDAD DE VIDA POSTERIOR A LA RECONSTRUCCIÓN DE LA ANASTOMOSIS EN PACIENTES CON CÁNCER DE RECTO: ESTUDIO INTERNACIONAL MULTICÉNTRICO DE COHORTE COMPARATIVO: ANTECEDENTES: Se puede considerar reconstruir la anastomosis en pacientes seleccionados con fuga persistente, estenosis o recidiva local. Esto es técnicamente desafiante y poco se sabe sobre los resultados funcionales después de este tipo de cirugía que rara vez se realiza. OBJETIVO: El objetivo de este estudio fue comparar resultados funcionales y la calidad de vida entre reconstrucción de la anastomosis y la anastomosis primaria exitosa posterior de la escisión total de mesorrecto (TME ) por cáncer de recto. DISEÑO: Este estudio fue diseñado como un estudio internacional multicéntrico de cohorte comparativo. ENTORNO CLINICO: El estudio se llevó a cabo en tres centros de referencia terciarios en Holanda, Bélgica y Francia. PACIENTES: Los pacientes sometidos a reconstrucción de anastomosis fueron comparados con pacientes con anastomosis primaria exitosa después de TME por cáncer de recto. PRINCIPALES MEDIDAS DE VALORACION: Los cuestionarios; Escala de Síndrome de Resección Anterior Baja ( LARS ), EORTC QLQ-C30, y QLQ-CR29, fueron utilizados para evaluar los resultados. RESULTADOS: En total, se incluyeron 170 pacientes; 52 reconstrucción de anastomosis y 118 controles. LARS ocurrió en el 73% posterior a la reconstrucción de la anastomosis en comparación con el 68% posterior a la anastomosis primaria exitosa ( p = 0, 52). El grupo de reconstrucción tuvo peores puntuaciones medias de EORTC QLQ-CR29 para incontinencia fecal ( p = 0, 03) y flatulencia ( p = 0, 008). No hubo diferencias en disfunción urinaria ( p = 0, 48) o sexual, ni en hombres ( p = 0, 83) ni en mujeres ( p = 0, 76). Se encontraron puntuaciones significativamente peores en el grupo de reconstrucción para salud global ( p = 0, 002), desempeño ( p = 0, 049) y función social ( p = 0, 006), imagen corporal ( p = 0, 03) y ansiedad ( p = 0, 02). LIMITACIONES: La limitación de este estudio es el posible sesgo de respuesta. CONCLUSIONES: La reconstrucción de la anastomosis se asocia con una calidad de vida significativamente peor en comparación con los pacientes con anastomosis primaria exitosa. Sin embargo, LARS fue comparable entre los grupos y no debería ser una razón para impedir la restauración de la continuidad intestinal en pacientes muy motivados. Consulte Video Resumen en http://links.lww.com/DCR/B565 .